Target based drug discovery for beta-globin disorders: Drug target prediction using quantitative modelling with hybrid functional Petri nets - Mehraei, Mani; Bashirov, Rza; Tüzmen, Şükrü (My University, 2016)
Recent molecular studies provide important clues into treatment of beta-thalassemia, sickle-cell anaemia and other beta-globin disorders revealing that increased production of fetal hemoglobin, that is normally suppressed in adulthood, can ameliorate the severity of these diseases. In this paper, we present a novel approach for drug target prediction for beta-globin disorders. Our approach is centered upon quantitative modelling of interactions in human fetal-to-adult hemoglobin switch network using hybrid functional Petri nets. In accordance with the reverse pharmacology approach we pose a hypothesis regarding modulation of specific protein targets that induce beta-globin and consequently fetal hemoglobin. Comparison of simulation results for the proposed strategy with the ones obtained for already existing drugs shows that our strategy is the optimal as it leads to highest level of beta-globin induction and thereby has potential beneficial therapeutic effects on beta-globin disorders. Simulation results enable verification of model coherence demonstrating that it is consistent with qPCR data available for known strategies and/or drugs.
Thıs article will be published in;Computational Biology and Chemistry (ISSN: 1476-9271) probably in 2016).
Keywords: Reverse pharmacology; Drug discovery; Fetal-to-adult hemoglobin switch network; Beta-thalassemia; Sickle-cell anaemia; Quantitative modelling; Hybrid functional Petri net